A Different Approach to Assess Oxidative Stress in Dengue Hemorrhagic Fever Patients Through The Calculation of Oxidative Stress Index - Edi Hartoyo; Iskandar Thalib; Cynthia Maharani Puspita Sari; Windy Yuliana Budianto; Eko Suhartono (Journal of Tropical Life Science, 2017)
The objectives of this study were to determine the involvement of Oxidative Stress (OS) in the pathogenesis of dengue hemorrhagic fever (DHF) through the analysis of oxidative stress Index (OSI). The levels of malondialdehyde (MDA), superoxide dismutase (SOD) and catalase (CAT) activity, and OSI were measured in 61 child dengue patients and (aged 6 months–18 years) with three different stages of DHF, i.e stage I, II, and III. The results show that the levels of MDA, SOD and CAT activity, and OSI significantly different between the group. The all parameters that investigated in this present study seems higher MDA level and OSI in the higher grade of DHF, except for SOD and CAT activity. From this result, it can be concluded that oxidative stress pathways might be involved in the pathomechanism of DHF and OSI might be used as a biomarker for OS and the severity in DHF patients.